Vibration control of midrise buildings by semi-active tuned mass damper including multi-layered soil-pile-structure-interaction. (September 2022) - Ghorbanzadeh, Mohammad; Sensoy, Serhan; Uygar, Eris
Abstract: Semiactive tuned mass dampers (STMD) can be used in mid-rise buildings to control seismic excitations during continuous operation. Numerous studies have been conducted to investigate the performance of STMDs without considering the soil-pile-structure interaction (SPSI). When modeled with a fixed base, the characterization of STMD can be significantly misleading and doesn't necessarily result in a conservative design. In order to evaluate the impact of SPSI on the performance of STMD under seismic loading, mid-rise steel buildings on layered soil were analyzed using the three-dimensional finite element software Opensees. The effects of changes in geotechnical parameters such as shear strength and stiffness were also studied. The results showed that the efficiency of STMD is significantly reduced and the structural accelerations and displacements are increased with the inclusion of SPSI. A progressive increase in the displacements of the top storeys were also observed when the SPSI effect was considered. The reduction in the base shear was attributed to the mobilised passive force around the piled foundations when SPSI was considered in the analysis models.